2013
DOI: 10.1186/2045-8118-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Culture models to study leukocyte trafficking across the choroid plexus

Abstract: BackgroundA critical point during the course of central nervous system infection is the influx of leukocytes from the blood into the brain across the blood-brain barrier (BBB) and the blood-cerebrospinal fluid barrier (BCSFB). However, experimental in vitro models to investigate leukocyte transmigration across cultured choroid plexus epithelial cells have been lacking so far.MethodsWe have developed a porcine and human “inverted” culture insert system that enables leukocyte transmigration specifically from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…4, Region C). The chosen frequency allows for resistance evaluation without effects on cell’s plasma membrane [69]. Further, at this frequency, previous analyses have showed that the impedance is dependent on the cell bodies, whereas at the lower or higher frequencies, parameters such as impedance of the electrode/electrolyte interface or the medium, and the constriction resistance of the working electrode dominate the impedance measurements [70].…”
Section: Resultsmentioning
confidence: 99%
“…4, Region C). The chosen frequency allows for resistance evaluation without effects on cell’s plasma membrane [69]. Further, at this frequency, previous analyses have showed that the impedance is dependent on the cell bodies, whereas at the lower or higher frequencies, parameters such as impedance of the electrode/electrolyte interface or the medium, and the constriction resistance of the working electrode dominate the impedance measurements [70].…”
Section: Resultsmentioning
confidence: 99%
“…Transepithelial electric resistance (TEER) across the Transwell was measured daily with an EVOM2™ Epithelial Voltohmmeter (World Precision Instruments, Sarasota, FL, USA) to test the integrity of HUVEC layer. 32 When the TEER value reached a plateau (i.e., when the HUVEC layer was confluent, typically 9 days after seeding), 50 μg of bare NP* or NP*-TA-alb were added to the apical side of the Transwell and incubated for 6 h. Subsequently, media in apical and basolateral sides were collected, and their fluorescence intensity was measured using a Synergy 4 Multi-Mode Microplate Reader (BioTek, Winooski, VT). The NP* or NP*-TA-alb in the medium of each side was determined using calibration curves drawn with each type of NPs suspended in the complete EGM-2 medium.…”
Section: Methodsmentioning
confidence: 99%
“…These models differ in terms of temporal and spatial resolution, and in their consideration of drug protein binding (710). For example, the combinatorial mapping approach has been recently introduced using unbound drug concentration with the brain slice technique (10,11). This approach can predict unbound drug CNS exposure at steady state in multiple brain compartments, but does not allow temporal characterization of drug concentration changes.…”
Section: Introductionmentioning
confidence: 99%